Production and Characterization of Biodiesel Using Nonedible Castor Oil by Immobilized Lipase from Bacillus aerius. - Narwal, Sunil Kumar; Saun, Nitin Kumar; Dogra, Priyanka; Chauhan, Ghanshyam; Gupta, Reena (BioMed Research International, 2015)
A novel thermotolerant lipase from Bacillus aerius was immobilized on inexpensive silica gel matrix. The immobilized lipase was used for the synthesis of biodiesel using castor oil as a substrate in a solvent free system at 55°C under shaking in a chemical reactor. Several crucial parameters affecting biodiesel yield such as incubation time, temperature, substrate molar ratio, and amount of lipase were optimized. Under the optimized conditions, the highest biodiesel yield was up to 78.13%. The characterization of synthesized biodiesel was done through FTIR spectroscopy, 1H NMR spectra, and gas chromatography.